Optimalisasi Desain Kemasan, Variasi Produk, dan Display Produk terhadap Keputusan Pembelian - Amanda, Chikal; Humairoh (BUDGETING : Journal of Business, Management and Accounting, 2025)
This study aims to determine the effect of packaging design, product variation, and display on purchasing decisions for Kobe products at Hypermart Lippo Karawaci. This study uses a quantitative approach with a population of customers who use Kobe products at Hypermart Lippo Karawaci, which is limited to 20-35 years old. The sampling technique used is non-probability sampling with a purposive sampling approach. The sample used is 100 respondents. The data analysis tool used is SPSS version 26. The results of this study indicate that partially, the packaging design variable, the product variation variable, has a positive and significant effect on purchasing decisions. In contrast, the product display variable positively and significantly affects purchasing decisions. Simultaneously (together), packaging design, product variation, and product display positively and significantly affect purchasing decisions. The results of the multiple determination coefficient test obtained an Adjusted R-Square value of 0.937 or 93.7%, indicating that the packaging design variable, product variation, and product display affect purchasing decisions by 93.7%, and the remaining 6.3% are influenced by other variables not examined in this study. The novelty of this research is that no research has jointly examined the fact that packaging design, product variation, and product display are important factors that can shape purchasing decisions. This study provides recommendations for retail stores, one of which is Hypermart Lippo Karawaci, to increase the competitiveness of Kobe products in the retail market.   Keywords: Packaging Design, Product Display, Purchasing Decision, Produk Variation